Career and family women's century-long journey toward equity - Goldin, Claudia Dale (Princeton University Press, 2021)
"In Career and Family, Claudia Goldin builds on decades of complex research to examine the gender pay gap and the unequal distribution of labor between couples in the home. Goldin argues that although recent public and private discourse has brought these concerns to light, the actions taken-such as a single company slapped on the wrist or a few progressive leaders going on paternity leave-are the economic equivalent of tossing a band-aid to someone with cancer. These solutions, Goldin writes, treat the symptoms and not the disease of gender inequality in the workplace and economy. Goldin points to data that reveals how the pay gap widens further down the line in women's careers, about 10 to 15 years out, as opposed to those beginning careers after college. She examines five distinct groups of women over the course of the twentieth century: cohorts of women who differ in terms of career, job, marriage, and children, in approximated years of graduation-1900s, 1920s, 1950s, 1970s, and 1990s-based on various demographic, labor force, and occupational outcomes. The book argues that our entire economy is trapped in an old way of doing business; work structures have not adapted as more women enter the workforce. Gender equality in pay and equity in home and childcare labor are flip sides of the same issue, and Goldin frames both in the context of a serious empirical exploration that has not yet been put in a long-run historical context. Career and Family offers a deep look into census data, rich information about individual college graduates over their lifetimes, and various records and new sources of material to offer a new model to restructure the home and school systems that contribute to the gender pay gap and the quest for both family and career"--